Insight Into Mouse Models of Hyperthyroidism - Zhang, Mengyu; Jiang, Wen; Lu, Ganghua; Wang, Ru; Lv, Zhongwei; Li, Dan (Frontiers in Endocrinology, 2022)
Hyperthyroidism is characterized by an increase in the synthesis and secretion of thyroid hormones in the thyroid gland and the most common cause of overproduction of thyroid hormones is Graves' disease (GD). Long-term disease model of hyperthyroidism has been set up. In general, methods to induce GD include transfection of fibroblasts, injecting plasmids or adenovirus containing thyroid stimulating hormone receptor (TSHR) or TSHR subunit, and exogenous artificial thyroid hormone supplementation. Delightfully, in mouse studies, novel treatments for GD and Graves’ Orbitopathy (GO) were discovered. It is reported that prophylactic administration of TSHR A subunit protein in genetically susceptible individuals could induce immune tolerance and provide protection for the future development of GD. Biologically active monoclonal antibody against intracellular adhesion molecule-1 (ICAM-1 mAb) and siRNA targeting TSHR can also be used to treat GD. Moreover, new potential therapeutic targets have been identified in mouse GO models, which could be a novel therapeutic approach. Besides, human placental mesenchymal stem cells (hPMSCs) into the orbit, fucoxanthin and icariin may be other new alternative therapies in addition to existing drugs, although further research is needed.